Social Interaction and Cultural Adaptation in the Utilization River Water - Qolbiana, Syifa Nur; Harjanti, Diah Trismi; Christanto, Ludovicus Manditya Hari (Universitas Tanjungpura, 2025)
This study explores the social interactions and cultural adaptation strategies of the Kampung Beting community in utilizing the Kapuas River water for daily life. Despite environmental challenges and water quality issues, the river remains a central element in the community